체험적 속성과 기능적 속성에 대한 소비자 제품평가 - 민병권(Byung-Kwon Min); 정용길(Yong-Gil Jung) (한국콘텐츠학회 논문지, 9(5), 2009)
This study proposes a theory of consumer experiences based on a cognitive science framework that serves as an alternative to the mainstream marketing paradigm of information processing and choice. The theory consists of three key theoretical constructs: experiential modules, primary vs. secondary experiences, and the hierarchy of experiential modules. Based on this theory, this study investigates the effect of experiential attributes and functional attributes on consumer's product evaluations, and the moderating role of consumer's knowledge. The main research findings are (1) the subjects react faster to sensory and affective stimuli(ex: experiential attributes) than they do to intellectual stimuli (ex: functional attributes), (2) the interaction modularity of attributes(functional vs. experiential) $×$ tempo(normal vs. fast) $×$ product knowledge(novice vs. expert) appear significantly with product evaluation as the dependent measure. 본 연구는 정보처리과정과 선택에 대한 주류 마케팅 패러다임에 대한 대안으로써 진화론적 관점의 인지과학에 기초한 소비자 체험이론을 제안하고 있다. 소비자 체험이론은 체험적 모듈, 일차단계체험 및 이차 단계체험, 그리고 체험모듈의 위계구조라는 3개의 이론적 구조로 구성되어 있다. 본 이론에 근거하여 본 연구는 소비자 제품 평가에 대한 체험적 속성과 기능적 속성들의 영향을 조사하고 있다. 주요 연구 결과는 다음과 같다. (1) 조사대상자들은 지적 자극(예: 기능적 속성)보다 감각적이고 감정적인 자극(예: 체험적 속성)에 대해 보다 빠르게 반응하였다. (2) 체험모듈 유형(기능적 vs. 체험적) $×$ 템포(정상 vs. 빠름) $×$ 제품지식(초보자 vs. 전문가)의 상호작용이 제품평가에 대해 발생하고 있다.